Genome-wide association study of copy number variation and early growth traits in inner Mongolian cashmere goats - Liu, Yifan; Xi, Haijiao; Xu, Qi; Zhou, Bohan; Li, Jinquan; Su, Rui; Lv, Qi; Zhang, Yanjun; Wang, Ruijun; Wang, Zhiying (Frontiers in Veterinary Science, 2025)
IntroductionThe early growth traits including birth weight (BW), weaning weight (WW), pre-weaning average daily gain (ADG) and yearling weight (YW) are crucial productivity indicators that directly influence growth rates of cashmere goats and economic income of herdsmen in the cashmere goat breeding programs. However, the genetic mechanism of these traits in Inner Mongolia Cashmere Goats (IMCGs) has not been elucidated.Copy number variation (CNV), as a prevalent form of genomic structural variation and a significant contributor to the genetic diversity, has emerged as a valuable molecular marker for analysis of complex traits.MethodsIn this study, Whole Genome Sequencing (WGS) data of 461 IMCGs were used to detect CNVs on autosomes and the Genome-Wide Association Study (GWAS) analysis based on CNVs was performed for early growth traits (BW, WW, ADG and YW) of IMCGs.The identified CNVs were further validated through PCR verification. In addition, t-test was performed on the phenotypes of individuals of IMCGs with significant CNVs.ResultsThe 26,003 non-redundant CNVs and 5,014 non-redundant CNVRs were detected, covering a total of 1,015.4 Mb (38.97 %) of the autosomal goat genome. The 11 CNVs were significantly associated with early growth traits through GWAS analysis, including two pleiotropic CNVs simultaneously influencing ADG and WW. Through integrated bioinformatics analysis, seven key candidate genes (ZN845, SOX15, FGF11, GPS2, DVL2, SPRY4 and STAT2) were identified as being associated with early growth traits.Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses demonstrated that these genes were primarily involved in biological pathways related to cell proliferation, differentiation and protein phosphorylation.Among the 11 significant CNVs, 9 CNVs were demonstrated to show significant associations with individual phenotypes.DiscussionThis study significantly expands the genomic CNV map of IMCGs through large-scale genotyping.The findings demonstrate the utility of CNV-based GWAS analysis in elucidating the genetic mechanisms underlying complex traits, providing valuable insights for molecular marker-assisted breeding and molecular genetic research of economically important traits in cashmere goats.